Pengaruh Jarak Waktu Pemberian Kejutan Dingin pada Pembentukan Individu Triploid Ikan Patin (Pangasius Sp) - Dwi Puji Hartono; Pindo Witoko (Politeknik Negeri Lampung., 2012)
The aim of this study was to know the effect of temperature shock gift time distance from fertilization on the triploidy individual process, persentage of hatching rate and survival rate of larva patin catfish. Temperature shock gift time distance treatment from fertilization process is given each 120 second, 180 second, 240 second and 300 second in temperature 40C during 90 second. Each treatment is done as much as 3 times. Hatch and larva maintenance is done in aquarium and hapa for fingerling activity. The result shows that temperature shock gift time distance treatment from fertilization process gives real result on the triploidy individual procces in patin catfish (p<0,05). Highest percentage triploidy individual is got in temperature shock gift time distance from fertilization process 180 second as big as 83,33 %. The growth level patin catfish day 28 show enhanced in line with individual percentage enhanced triploidy from each treatment. The highest growth rate is got from temperature shock gift time distance treatment from fertilization process as big as 11,13 %. Keywords: catfish, triploidy, time distance, temperature shock